Edukasi Pencegahan Hipertensi dan Pemeriksaan Tekanan Darah pada Kelompok Masyarakat Lansia di Desa Borisallo, Kab. Gowa - Arni Isnaini Arfah; Wardiah Hamzah Syam; Nurulmy Mahmud (Compromise Journal Community Proffesional Service Journal, 2025)
Hypertension is one of the health problems that are often experienced by the elderly. This is caused by various factors such as an unhealthy lifestyle, an unbalanced diet, and a lack of physical activity. Hypertension can result in stroke, heart disease, kidney disorders, and can even result in death. The elderly need to know how to prevent hypertension. The number of elderly people in Borisallo Village, Parangloe District, Gowa Regency is around 310 people (10.75%). The partner in the PKM of the Assisted Village is Borisallo Village which fosters the elderly in its area. Based on the problems faced by partners, the PKM service program of the Assisted Villages that is expected to be a solution is (1) Education on the prevention of hypertension in the elderly (Elderly), (2) Blood pressure checks in the elderly in Borisallo Village. This activity is financed by the UMI Waqf Foundation.  The results of the implementation of PKM in the Assisted Villages (1) Counseling on the prevention of hypertension in the elderly community has been carried out at the Borisallo Village Hall which was attended by 15 elderly people, (2) Then continued with a hypertension examination showing that in general, the blood pressure of the elderly community in Borisallo Village, Parangloe District, Gowa Regency, is still normal unless there are as many as 2 (20%). It is recommended to have comprehensive and periodic health checks on the elderly, not only hypertension, but more comprehensive, including mental health, so that the health status of the elderly can be known